PENGARUH PENERAPAN TEKNIK SPOTLIGHT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 MUARA BUNGO - Sari, Rina Busrina; Aima, Zulfitri; Harisman, Yulyanti (Pendidikan Matematika, 2013)
Background of this research is comprehension of concept studied mathematic at student SMPN 4 Muara Bungo class VIII is still low. The purpose of this research is to know what is studied comprehension of concept student with spotlight technique is good than conventional study at SMPN 4 Muara Bungo class VIII. Kinds of this research is experimental research with hypothesis p-value is 0,005, so hypothesis is receive. So that can concluded that comprehension of concept with spotlight technique is good than comprehension of concept with conventional study at SMPN 4 class VIII Muara Bungo